2013
DOI: 10.1111/jocn.12042
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term urinary catheter users self‐care practices and problems

Abstract: Aims The aims were to characterize a sample of 202 adult community-living long-term indwelling urinary catheter users, to describe self-care practices and catheter problems, and to explore relationships among demographics, catheter practices, and problems. Background Long-term urinary catheter users have not been well studied, and persons using the device indefinitely for persistent urinary retention are likely to have different patterns of catheter practices and problems. Design The study was a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 15 publications
1
83
1
2
Order By: Relevance
“…The information for this report is based on the detailed minutes from 163 team meetings and recruitment reports, as well as personal recollections. A full description of the sample at the beginning of the study has been published (Wilde et al, 2013), and the analysis of major outcomes are underway and will be described elsewhere.…”
Section: Overview Of Studymentioning
confidence: 99%
“…The information for this report is based on the detailed minutes from 163 team meetings and recruitment reports, as well as personal recollections. A full description of the sample at the beginning of the study has been published (Wilde et al, 2013), and the analysis of major outcomes are underway and will be described elsewhere.…”
Section: Overview Of Studymentioning
confidence: 99%
“…Even fewer studies have looked at the experiences and perceptions of those living with a suprapubic catheter. [11][12][13][14][15] In these studies, the authors say relatively little about how patients compared living with the 2 types of catheters or how the decision was made to have a suprapubic catheter rather than a urethral one. The primary aims of our study were to explore men's and women's perceptions of living with a urethral or suprapubic catheter, to examine how they decided to have a suprapubic catheter, and to compare their experiences of having a suprapubic catheter with their experiences of living with a urethral catheter.…”
mentioning
confidence: 97%
“…While many catheter users have spinal cord injury (SCI) or multiple sclerosis (MS), the population also includes those with other neurological disorders, diabetes, or disease/injury to the bladder region. Unfortunately, indwelling urinary catheters are seldom trouble free (Cottenden et al, 2013; Wilde, McDonald et al, 2013). Data collected in a longitudinal study of 43 long-term catheter users indicated that recurrent problems affect the great majority.…”
mentioning
confidence: 99%
“…Prevalence rates during eight months of catheter use were 70% for catheter-associated urinary tract infection (CAUTI) with a rate of 8.4/1000 catheter days; 74% for blockage; and 33% for catheter expulsion or dislodgement (Wilde, et al, 2010). For a two-month period prior to the beginning of this randomized clinical trial (RCT), catheter problems were reported as: 31% for CAUTI, 24% blockage, and 12% dislodgment (Wilde, McDonald et al, 2013). …”
mentioning
confidence: 99%
See 1 more Smart Citation